The far tribes ; Yellowstone - Wheeler, Richard S. (Wheeler, Richard S. Skye's West., 2015)
The far tribes: "Elkanah Morse came west from Lowell, Massachusetts with one goal in mind: to study the ways of the far tribes. Entrance into their world is not easy, though, and only one man is capable of bringing him to the natives safely, only one man who knows exactly what to bring for trade: Barnaby Skye. But Skye's advice is not enough. When rumors begin to spill that Morse is being held captive by one of the most vicious tribes in the mountains, Barnaby Skye feels compelled to take to the mountains and rescue the man...but he must face his most brutal battle yet" --